Intracranial hypertension associated with complex dural fistula after trau- matic brain injury, cerebral venous thrombosis and venous stenosis - Torres, Danielle Mesquita; Rossi, Matheus Andrighetti; Queiroga, Morgana Feitosa de; Rabelo, Samia Thabida de Oliveira; Severo, Reed Andre Siqueira; Silva, Henrique Coelho; Rocha, Felipe Araújo; Mont’ Alverne, Francisco Jose Arruda; Pitombeira, Milena Sales (Headache Medicine, 2023)
Full abstract in PDF.